2019
DOI: 10.1096/fj.201801706rr
|View full text |Cite
|
Sign up to set email alerts
|

Sema3E/PlexinD1 signaling inhibits postischemic angiogenesis by regulating endothelial DLL4 and filopodia formation in a rat model of ischemic stroke

Abstract: Angiogenesis is a crucial defense response to hypoxia that regulates the process of raising the promise of long‐term neurologic recovery during the management of stroke. A high expression of antiangiogenic factors leads to the loss of neovascularization capacity in pathologic conditions. We have previously documented an impairment of the cerebral vessel perfusion and neovascularization in the cortex neighboring the stroke‐induced lesion, which was accompanied by an activation of semaphorin 3E (Sema3E)/PlexinD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 56 publications
0
13
0
1
Order By: Relevance
“…The percentage volume loss was calculated as (contralateral hemispheric volume – Ipsilateral hemispheric volume)/(contralateral hemisphere volume) × 100%. [ 50 ]…”
Section: Methodsmentioning
confidence: 99%
“…The percentage volume loss was calculated as (contralateral hemispheric volume – Ipsilateral hemispheric volume)/(contralateral hemisphere volume) × 100%. [ 50 ]…”
Section: Methodsmentioning
confidence: 99%
“…Recently, many studies have reported the emerging effects of PLXND1 in the cardiovascular system 27,[35][36][37] ; particularly, a study by Ellie Tzima and colleagues described that PLXND1 functions as an endothelial mechanosensor and regulates vascular function and the site-specific distribution of atherosclerosis. 35 This finding suggests that a systematic summary of the emerging role of PLXND1 in cardiovascular development and disease, as well as the possible molecular mechanisms, is urgently needed.…”
Section: Studies Investigatingmentioning
confidence: 99%
“…100 Angiogenesis is a crucial defence against hypoxia and regulates the process of long-term neurologic recovery during the management of stroke. 36 The model of vessel sprouting demonstrated that new branches in angiogenesis were spearheaded by tip cells. 101 Only high expression of DLL4 in ECs determines tip cell selection.…”
Section: Involvement Of Plxnd1 In Ischaemic Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Studies with Sema 3E −/− mice revealed the important role that avascular zones generated by Sema3E play in guiding cardiac vessel development (48). Further, in a rat model of ischemic stroke, it was shown that Sema3E/Plexin-D1 signaling inhibited angiogenesis through regulation of endothelial dynamic deltalike 4 molecule (64).…”
Section: Role Of Semaphorins In Angiogenesismentioning
confidence: 99%